Answer:
3x +y -18 = 0
Explanation:
The equation of the perpendicular line can be formed from the given equation by swapping the x- and y-coefficients, and negating one of them. The constant in the new equation will be the constant necessary to make the line pass through the given point.
__
swapped coefficients
3x +y +c = 0 . . . . . now both coefficients are positive
new constant
We want c such that the equation is satisfied at the point (x, y) = (9, -9):
3(9) +(-9) +c = 0
27 -9 +c = 0
c = -18
equation of perpendicular line
The equation of the desired line is ...
3x +y -18 = 0